In Silico Bees - Devillers, James (Taylor & Francis, 2014)
Bees are critically important for ecosystem function and biodiversity maintenance through their pollinating activity. This book provides a collection of computational methods to those primarily interested in the study of the ecology, ethology, and ecotoxicology of bees. It presents numerous case studies to enable readers to understand the appropriateness but also the limitations of models in theoretical and applied bee research. Written by an international team of experts, this book covers the main types of modeling approaches that can be used in terrestrial ecology and applied ecotoxicology.